THE IMPACT OF PARTICULAR CHEMICALS IN CLOTHING ON HUMAN HEALTH — SUMMARY OF RECENT FINDINGS - Justyna Tasior; Karolina Kasprzak; Małgorzata Kuczek; Aleksandra Wiśniewska; Julia Marek; Mateusz Jasiński; Michał Szalach; Aleksandra Żywicka; Bartosz Burda (International Journal of Innovative Technologies in Social Science, 2025)
Recent studies clearly indicate that textile contamination with hazardous chemicals increasingly poses an emerging public health concern. Beyond its significant environmental implications, such contamination may lead to a variety of adverse health effects, including allergic skin reactions and an increased risk of autoimmune, metabolic, and oncological diseases. This comprehensive review highlights key chemical groups of concern frequently found in textiles that come into direct and prolonged contact with the skin, including heavy metals, per- and polyfluoroalkyl substances (PFAS), phthalates, and bisphenols. Their concentration in textiles, potential for bioaccumulation, and associated toxicological effects are concisely discussed in the context of human exposure and overall health risk. The following review synthesizes secondary data extracted from environmental studies, systematic reviews and meta-analyses obtained from PubMed between 2017 and 2025. The primary aim of this review is to present the current state of knowledge regarding the amounts, associated risks, and potential health effects of these chemicals.